Food, Drink and the Other: Producing Satire and Otherness in Portuguese Literature - Viera de Andrade, Constança (Topiques, études satoriennes / Topoï Studies, Journal of the SATOR, 2021)
Portuguese narrative fiction is plentiful of food and drink references, which vary in meaning and function accordingly to the historical context of production. The peripathetic Portuguese brought culinary knowledge from abroad mainly since the 16th century, merging cultural changes of food and drink with practices from their country of origin. This was a turning point in the history of Portuguese narrative fiction, for it made more present the concept of the "other" through consumption habits. An extremely short travel between 16th and 19th narrrative fiction examples intends to highlight some uses of food and drink as topoi in historical and cultural context, asserting the relevance of this resource to articulate identities and alterities.